Ornamentalism - Cheng, Anne Anlin (Oxford University Press, 2019)
Focusing on the cultural and philosophic conflation between the 'oriental' and the 'ornamental', Ornamentalism offers an original and sustained theory about Asiatic femininity in western culture.